How to become an ethnobiologist: against the cultural monopoly - Albuquerque, Ulysses Paulino (Ethnobotany Research and Applications, 2022)
In this note, I construct a narrative that defends the interdisciplinary aspect of ethnobiology based on my experience as ethnobiologist. While I point out the criticisms that the discipline receives, I undertake an exercise of self-criticism, defending that the divergences that exist in the discipline can be overcome with a real understanding of its nature. Keywords: Brazilian anthropology, ethnobiology, ethnoscience.